Mathematics e-comic in cultural context to improve student motivation and learning outcomes - Farhan, Dani; Ikhsan, M; Elizar, Elizar (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Introduction: Learning media is a key factor that influences student motivation and learning outcomes. The learning media used should be relevant to students' daily lives, including cultural aspects. One example is the use of digital comics (e-comics) in mathematics, particularly in a cultural context, for teaching material on Systems of Linear Equations in Two Variables (SLETV).Aim: This study aimed to determine the characteristics of mathematical e-comics in a cultural context that are valid, practical, and effective in increasing motivation and learning outcomes among junior high school students.Method: The research used a development method based on the Plomp model, which consists of an initial investigation, design, and assessment stage. The subjects were class VIII students at an Islamic junior high school in West Aceh, Indonesia.Result: The validity scores for the content and media were 4.70 and 4.64, respectively, showing a very high level of validity. Practicality was measured by teacher responses (4.43) and implementation levels (4.21), both indicating very feasible use. The effectiveness was assessed through a Learning Outcomes Test (LOT), student responses, and motivation questionnaires. LOT results showed 82.05% of students achieved the Minimum Mastery Criteria (KKM), 80.19% of students gave positive responses, and motivation scores reached 83.86%, indicating very good levels.Conclusion: This research developed a culturally relevant mathematical e-comic for SLETV material, which was found to be valid, practical, and effective in enhancing student motivation and learning outcomes in junior high school. The results suggest that incorporating cultural contexts in digital learning media can positively impact student engagement and achievement.